Pelatihan Penggunaan Aplikasi Publish Or Perish (POP) Untuk Mencari Referensi Jurnal Pada Mahasiswa Universitas Muhammadiyah Jambi - Dani, Rian; Veronica, Deka; Irmanelly Irmanelly; Asrini Asrini (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Every student has the ability to write scientific papers, but in reality there are still many students who have difficulty. This is due to the limited ability of students to access references, as experienced by students at Muhammadiyah University in Jambi. Publish or Perish (PoP) is an application that can help students find references. Therefore, this service activity is carried out with the aim of providing training to students to improve students' abilities in writing scientific papers through Publish or Perish (PoP). The training activity began with the delivery of material on the importance of using Publish of Perish (PoP) in writing scientific papers. Introduction to the Publish or Perish (PoP) application. Delivery of material with lectures, questions and answers. Then carry out practice in the form of downloading the Publish or Perish (PoP) application on the desktop, installing the Publish or Perish (PoP) application. Operate the Publish or Perish (PoP) application. The conclusion from this PKM activity is that the majority of activity participants who are students at Muhammadiyah University of Jambi are able to use the Publish or Perish (PoP) application well.